4-2x-X=13

Simple and best practice solution for 4-2x-X=13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-2x-X=13 equation:


Simplifying
4 + -2x + -1X = 13

Reorder the terms:
4 + -1X + -2x = 13

Solving
4 + -1X + -2x = 13

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -1X + -4 + -2x = 13 + -4

Reorder the terms:
4 + -4 + -1X + -2x = 13 + -4

Combine like terms: 4 + -4 = 0
0 + -1X + -2x = 13 + -4
-1X + -2x = 13 + -4

Combine like terms: 13 + -4 = 9
-1X + -2x = 9

Add '2x' to each side of the equation.
-1X + -2x + 2x = 9 + 2x

Combine like terms: -2x + 2x = 0
-1X + 0 = 9 + 2x
-1X = 9 + 2x

Divide each side by '-1'.
X = -9 + -2x

Simplifying
X = -9 + -2x

See similar equations:

| 8=-6x+8x | | 2x-4(x+1)=-2(x+2) | | 18k=-216 | | 0=0.2x^2-1.3x+3 | | 0.5*x-sin(x)=0 | | -5+2x-3x=-13 | | 5x+32=5x+9 | | 0.5*(x)-sin(x)=0 | | y^2+4x^2-32x=4y-64 | | 4x+3(4x-5)=-127 | | [5*(5a-5)-120]*5-25=125 | | sin(x)-0.5*(x)=0 | | (4m-18)=12 | | 1.86g-4=0.65 | | 2a-8+-1a=-4 | | (5b+11)=19 | | -108=3(4n-4) | | 9x^2+49y^2=392y-343 | | 2(x^2-2x+8)+3x^2-5x-9= | | -112=8(-6+8x) | | y=15x+75 | | 2x=10x+-40 | | 8x-x(x-5)=x+25 | | 23=5+2n-8n | | 3x+10=2(4x+50) | | 16=4m+4 | | -7y=14x | | -9=-4x-5x | | 8+3x=2x | | -8x+20y+4x^2=7-4y^2 | | 0=x^2+22x+112 | | 4(g+2)=2(4-g) |

Equations solver categories